First flush loading of pollutants from urban storm runoff in Skudai, Johor - Rahmat, Siti Nazahiyah (2007)
Runoff of eight storm events from residential (3.34 ha) and six events from commercial (0.75 ha) catchments were sampled to investigate the first flush phenomenon. The first flush was analysed by plotting the cumulative loading ratio against cumulative runoff ratio. The degree of flushing was higher in the commercial catchment as reflected by more points fall above the bisector line. Results indicated that the first flush phenomenon was greater in the smaller catchment. For the commercial catchment, the first 20 - 30% of the flow evacuated between 20-70% COD, 22-74% SS, 24-68% N03-N, 7-69% NH3-N and 22-87% P. For the residential catchment, the first 20 - 30% of the discharges evacuated between 15-69% COD, 15-78% SS, 14-49% NO3-N, 23-53% NH3-N and 23-43% P. For both catchments, no correlation was found between the pollutant concentration and the antecedent dry weather period.